THE INFLUENCE OF EARTHWORM MEAL IN FEED TO HEMOGLOBIN LEVEL AND ERYTHROCYTE INDEX OF MALE LANDRACE PIGLETS AFTER WEANING - Pertiwi, Ni Made Dwi Adnyana; Ardana, Ida Bagus Komang; Kartini, Ni Luh (Buletin Veteriner Udayana; Vol. 14 No. 1 February 2022DO - 10.24843/bulvet.2022.v14.i01.p08, 2022)
Pigs are beneficial livestock that are maintained by many people, besides that one of the factors that determine the success of these livestock is nutrition, one of which uses feed with a mixture of earthworm flour ( Lumbricus rubellus ) where good nutrition affects livestock conditions, one of which is hemoglobin and erythrocyte index. The purpose of this study was to determine the effect of giving earthworm flour to the hemoglobin level and index of male erythrocyte erythrocytes after weaning. This study used a Completely Randomized Design (CRD) using 24 male landrace piglets after weaning. The treatment given was divided into four groups of each control group (P0), the group with the giving of earthworm flour by 4 g (P1), the group by giving earthworm flour by 8 g (P2), the group by giving earthworm flour by 16 g (P3). Calculation of hemoglobin level and erythrocyte index was carried out before administration of earthworm flour and after giving with a span of one month was carried out to see the effect of feed mixed with earthworm flour. The results of the variation analysis showed that the hemoglobin level of each group: 10,55; 10.83; 13.83; and 10.93 (g / dL) and the erythrocyte MCV index 59.45; 61.70; 60,61; and 59.56 (fL), MCHC 39.56; 39,15; 39,40; and 38.68 (g / dL). The results showed that the administration of earthworm flour was not significantly different from the hemoglobin level and erythrocyte index. The conclusion of this study is that the administration of earthworm flour in feed does not increase hemoglobin levels and has no effect on the erythrocyte index but is able to stabilize its value so that it is still in normal numbers.